The Role of Education in Improving UMKM Performance in Handmade Batik in Tanjung Bumi District, Bangkalan Regency - Muhamad Hofi; Romiftahul Ulum (Journal of Practice Learning and Educational Development, 2025)
Micro, small, and medium-sized enterprises, or MSMEs, are critical to economic expansion. This study's goal is to ascertain how education affects MSME's capacity batik tulis actors in Tanjung Bumi to manage their businesses. Education is a very important element in strengthening MSMEs. Semi-structured interviews are performed to acquire data for the qualitative research approach. Four MSME owners participated in this study as informants. Data flow analysis methods were used to the data. The study's findings show that education has a major role in improving the quality of MSMEs from a number of angles, including education, business management, marketing, financial management, and technology and innovation.